Structural studies of ER-associated protein quality control systems - Robson-Tull, J (2023)
ER-associated protein degradation (ERAD) is an important degradation pathway for the removal of misfolded proteins from the endoplasmic reticulum (ER). This pathway encompasses a set of evolutionary conserved mechanisms for the selection, ubiquitination and retrotranslocation of membrane and lumenal proteins from the ER to the cytosol. Recent structural studies of the yeast Hrd1 E3 ligase complex identified a possible mechanism by which ERAD substrates are retrotranslocated across the ER membrane. Yeast Hrd1 forms a heterodimer with the rhomboid pseudoprotease Der1, each of which is proposed to contribute a half-channel in the membrane for retrotranslocation. Crosslinking studies also support this hypothesis. However, the mechanisms for selection of membrane substrates are still unknown and the identity of the translocon in other ERAD pathways remains elusive. This is further hindered by a lack of structural studies, especially in mammalian systems.